Foam Behaviour of An Aqueous Solution of Piperazine- N-Methyldiethanolamine (MDEA) Blend as A Function of The Type of Impurities and Concentrations - Iwan Ratman; Tutuk Djoko Kusworo; Ahmad Fauzi Ismail (International Journal of Science and Engineering, 2010)
This study focuses on the effect of impurities in the natural gas stream on the characteristic of foam behaviour in the blended piperazine and MDEA solution. Hydrocarbon liquids, Iron Sulphide, Sodium Chloride, Acetic Acid, Methanol and Polyethylene Glycol were used as the impurities. The results indicated that the type of impurities determined the foam formation of the amine solution. The concentration of piperazine-MDEA blends also enhanced to the increasing of the foam height of blended piperazine-MDEA. Iron sulfide, hydrocarbon and sodium chloride are the impurities which apparently contributed to the high foaming tendency of the solutions. At the same concentration of the impurities, iron sulfide appeared as the most influential contaminant to the foam formation, which promoted the highest foamability in any concentrations of the blend piperazine-MDEA